2011
DOI: 10.1111/j.1574-6968.2010.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

A HupS-GFP fusion protein demonstrates a heterocyst-specific localization of the uptake hydrogenase in Nostoc punctiforme

Abstract: All diazotrophic filamentous cyanobacteria contain an uptake hydrogenase that is involved in the reoxidation of H(2) produced during N(2) -fixation. In Nostoc punctiforme ATCC 29133, N(2) -fixation takes place in the microaerobic heterocysts, catalysed by a nitrogenase. Although the function of the uptake hydrogenase may be closely connected to that of nitrogenase, the localization in cyanobacteria has been under debate. Moreover, the subcellular localization is not understood. To investigate the cellular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Most uptake hydrogenases investigated so far are rapidly inhibited by molecular oxygen (13), and a cyanobacterial uptake hydrogenase localized in the vegetative cells would undoubtedly be inactivated by photosynthetic oxygen evolution (14). Recently, it was demonstrated that the active enzyme is produced solely in heterocysts under N 2 -fixing conditions (19). The maturation system and genomic context of HupSL in N. punctiforme have been investigated extensively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most uptake hydrogenases investigated so far are rapidly inhibited by molecular oxygen (13), and a cyanobacterial uptake hydrogenase localized in the vegetative cells would undoubtedly be inactivated by photosynthetic oxygen evolution (14). Recently, it was demonstrated that the active enzyme is produced solely in heterocysts under N 2 -fixing conditions (19). The maturation system and genomic context of HupSL in N. punctiforme have been investigated extensively.…”
mentioning
confidence: 99%
“…The maturation system and genomic context of HupSL in N. punctiforme have been investigated extensively. The hupSL promoter region and binding sites for the transcriptional regulator NtcA have been identified (20); the extended hyp operon region, comprising the assembly and maturation system of HupSL, has been shown to be regulated by the transcriptional regulator CalA (19); and HupW, a protease needed for the cleavage of a C-terminal peptide from the large subunit HupL, has been shown to be transcribed in N 2 -fixing cultures (20). In a related organism, Nostoc (Anabaena) sp.…”
mentioning
confidence: 99%
“…Heterocysts contain two distinct O 2 -sensitive Ni–Fe hydrogenases defined by their physiological role (Table 2). One is termed uptake hydrogenase, which is encoded by the hupSL operon and catalyzes the irreversible conversion of H 2 into protons and electrons, while the second enzyme is a bidirectional hydrogenase, which catalyzes the reversible conversion of protons and electrons into H 2 and is encoded by hoxEFUYH [152,192,193,194,195,196,197].…”
Section: Metalloproteins In N2 Fixation and H2 Metabolismmentioning
confidence: 99%